KONTRIBUSI PEMIKIRAN IMAM SYATHIBI DAN ABRAHAM H. MASLOW TENTANG KEBUTUHAN DASAR MANUSIA - Yusuf Yahya (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2020)
The five basic needs of human to formulate the laws and regulations related to protectionof one’s religion, his soul, hisself, his offspring, his goods and his mind, as it was recognized by Syatibi’s theory called al-Masalihadh-Dharuriyyah (basic protected human needs) have been enhanced by Abraham H. Maslow. Every one of humans after being protected by the law, he should be capable of enhancing such five principles .When one’s religionwas protected from intimidation and violence, protected to do all the given orders and to leave all the given prohibitions in his religion as what Syatibi asserted, thus, at the same time the human should need his five basic needs called physiological needs to be fulfilled, such as need of air or oxygen to breath, need for foods and water, sexual desire, and having break, etc. Again, all these basic needsmust be fulfilled. Otherwise if they do not happen, one’s belief should get a trouble, and his convenience would be threatened for his own obedience of his belief or of his religion. That is because he would convert to get busier in order to fulfill his own basic needs. When one could feel safe on the first level, he would rise to the upper level where his self and his soul are protected under safe and convenience as it was intended by Syatibi. Maslow also means that a person on this gratification level needs to be safe (safety need). A person is given a ptotection of the law to care himself and his soul from murder, intimidation as well as violence. Hence, that is what intended by Maslow: a human must have a safe sense including safe in his neighborhood, his family and hisself.